2014
DOI: 10.1159/000369108
|View full text |Cite
|
Sign up to set email alerts
|

Novel Deletion of <b><i>SERPINF1</i></b> Causes Autosomal Recessive Osteogenesis Imperfecta Type VI in Two Brazilian Families

Abstract: Autosomal recessiveosteogenesis imperfecta (OI) accounts for 10% of all OI cases, and, currently, mutations in 10 genes (CRTAP, LEPRE1, PPIB, SERPINH1, FKBP10, SERPINF1, SP7, BMP1, TMEM38B, and WNT1) are known to be responsible for this form of the disease. PEDF is a secreted glycoprotein of the serpin superfamily that maintains bone homeostasis and regulates osteoid mineralization, and it is encoded by SERPINF1, currently associated with OI type VI (MIM 172860). Here, we report a consanguineous Brazilian fami… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(8 citation statements)
references
References 31 publications
1
5
0
1
Order By: Relevance
“…The presence of high consanguinity or a founder effect can change the prevalence of a disease among different populations, as described by Bardai et al (2016), who found the majority of mutations to be in the SERPINF1 and CRTAP genes among those who are related with a recessive pattern. Minillo et al (2014) also found the same SERPINF1 gene mutation in two unrelated Brazilian families, one of them with at least four generations of affected patients and reporting high consanguinity, supporting the hypothesis of a founder effect. In our study, mutations were identified neither in the SERPINF1 or CRTAP, nor in the PPIB , SERPINH1 , WNT1 or SP7 genes, suggesting that mutations in these genes are rare in the studied sample.…”
Section: Discussionsupporting
confidence: 66%
“…The presence of high consanguinity or a founder effect can change the prevalence of a disease among different populations, as described by Bardai et al (2016), who found the majority of mutations to be in the SERPINF1 and CRTAP genes among those who are related with a recessive pattern. Minillo et al (2014) also found the same SERPINF1 gene mutation in two unrelated Brazilian families, one of them with at least four generations of affected patients and reporting high consanguinity, supporting the hypothesis of a founder effect. In our study, mutations were identified neither in the SERPINF1 or CRTAP, nor in the PPIB , SERPINH1 , WNT1 or SP7 genes, suggesting that mutations in these genes are rare in the studied sample.…”
Section: Discussionsupporting
confidence: 66%
“…Autosomal-recessive homozygous identifies homozygous variants that are shared by all affected individuals and excludes variants that are homozygous in an unaffected individual [Hoover-Fong et al, 2014;Migliavacca et al, 2014;Moldenhauer Minillo et al, 2014];…”
Section: Phenodb Variant Analysis Toolmentioning
confidence: 99%
“…Each inheritance pattern follows a different set of rules: Autosomal‐recessive compound heterozygous includes only the heterozygous variants identified in the proband (assumed to be affected); if there is more than one affected family members, the analysis include only the variants that are identified in all affected members; next, the analysis includes only the genes that have more than one variant in the proband but if the same set of variants in a gene is found in one of the parents or in other unaffected family member then this gene (and its variants) is excluded of the analysis (Fig. A) [Hoover‐Fong et al., ; Sobreira et al., ]; Autosomal‐recessive homozygous identifies homozygous variants that are shared by all affected individuals and excludes variants that are homozygous in an unaffected individual [Hoover‐Fong et al., ; Migliavacca et al., ; Moldenhauer Minillo et al., ]; X‐linked recessive excludes X‐linked variants found in a related unaffected male but retains X‐linked heterozygous variants present in unaffected females; Autosomal‐dominant new mutation excludes heterozygous variants that are also identified in a parent [Gripp et al., ]; Autosomal–dominant inherited mutation retains heterozygous variants that are shared by affected individuals and excludes those found in unaffected individuals. Here, the submitter also has the option of looking for variants shared not only by all the affected individuals but by a subset of them, accounting for errors including misclassification as affected or failure to identify a variant by the WES/WGS in one of the affected individuals; Autosomal‐dominant variants retains heterozygous variants with a minor allele frequency (MAF) less than the threshold selected for the 1000 Genome and Exome Variant Server and excludes variants found in a particular version(s) of dbSNP database, if any is selected [Gripp et al., ].…”
Section: Phenodb Variant Analysis Toolmentioning
confidence: 99%
“…Subsequently, the genetic identification of SERPINF1 variants showed it to form 6 % of the OI population ( Glorieux et al, 2002 ; Land et al, 2007 ). The studies report small case series from different populations ( Cho et al, 2013 ; Glorieux et al, 2002 ; Homan et al, 2011 ; Minillo et al, 2014 ). In our large population study, 18 SERPINF1 cases with ten variants formed 12.5 % of the OI population from the Indian subcontinent.…”
Section: Discussionmentioning
confidence: 99%